Biomass distribution and physiological performance in cocoa genotypes: ecophysiological perspectives - Tezara, Wilmer (2025)
The relationship between growth analysis and biomass distribution and photosynthesis in the nursery phase of cacao seedlings is limited. The objective was to determine the morphological differences, biomass distribution, and physiological performance of seedlings from eight cacao genotypes (EETP-800, EETP-801, CCN-51, PMA 12, PMA 14, EETP-802, EETP-804, and APROCANE) under nursery conditions. Allometric measurements (height, stem diameter, and number of leaves), biomass distribution to different plant organs, growth analysis, and physiological parameters (photosynthesis rate, A; transpiration, E; stomatal conductance, gs; water use efficiency, WUE; water potential, Ψ; leaf area index, LAI; and chlorophyll content) were evaluated. Significant differences were found in root, stem, and leaf dry biomass, relative growth rate (RGR), net assimilation rate (NAR), leaf area ratio, specific leaf area, leaf weight ratio, and physiological parameters among the different genotypes. The highest RGR was found in the EETP-800 genotype (0.024 d-1), followed by PMA14, CCN-51, and EETP-801 (0.013–0.015 d-1); these rates are considerably low compared to other tropical crops. No correlations were found between RGR, NAR, and A. The results suggest that high genetic variability in cacao genotypes is expressed in morphological and physiological differences, as well as ingrowth and biomass distribution. .